2023
DOI: 10.1002/mpr.1958
|View full text |Cite
|
Sign up to set email alerts
|

Design and field procedures for the clinical reappraisal of the Composite International Diagnostic Interview version 3.3 in Qatar's national mental health study

Abstract: Background: The Composite International Diagnostic Interview (CIDI) has been clinically reappraised in several studies conducted mainly in the US and Europe. This report describes the methodology used to conduct one of the Middle East's largest clinical reappraisal studies. The study was carried out in conjunction with the World Mental Health Qatar-the first national psychiatric epidemiological study of common mental disorders in the country. This study aimed to evaluate the diagnostic consistency of core modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We used the latest version (3. As described in another manuscript published in this journal issue (Khaled, Amro, Abdelkader, et al, 2024), blind clinical reinterviews using the Structured Clinical Interview for DSM-5 (SCID) (First et al, 2015) found generally good concordance between WMH-CIDI-5 diagnoses and SCID diagnoses (AU-ROC from 0.67 to 0.81). Comorbid disorders were defined as the number of disorders, exactly 1, exactly 2, and 3 or more.…”
Section: Lifetime Prevalence Of Mental Disordersmentioning
confidence: 94%
“…We used the latest version (3. As described in another manuscript published in this journal issue (Khaled, Amro, Abdelkader, et al, 2024), blind clinical reinterviews using the Structured Clinical Interview for DSM-5 (SCID) (First et al, 2015) found generally good concordance between WMH-CIDI-5 diagnoses and SCID diagnoses (AU-ROC from 0.67 to 0.81). Comorbid disorders were defined as the number of disorders, exactly 1, exactly 2, and 3 or more.…”
Section: Lifetime Prevalence Of Mental Disordersmentioning
confidence: 94%
“…Briefly, the survey was conducted via telephone interviews and targeted Arabic-speaking residents of Qatar (Khaled et al, 2023). A stratified multi-stage sampling procedure was used to draw a representative sample of Qatari nationals and non-Qatari (Arab) residents for the study sample (Khaled et al, 2023). The survey was directed to male and female respondents aged 18 and above who lived in Qatar during the survey reference period.…”
Section: Study Sample-cidi Survey Samplementioning
confidence: 99%
“…As detailed in the companion paper, the main WMHQ sampling design is described elsewhere in this issue (Khaled et al, 2023).…”
Section: Study Sample-cidi Survey Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The second component comprised a clinical reappraisal, which was carried out using telephone follow‐up interviews of a subset of the original survey interviews ( n = 485) to assess the diagnostic consistency of core modules of the newly translated and adapted Arabic version of the CIDI against independent clinical diagnoses by trained clinicians based on the Structured Clinical Interview for DSM‐5 (Amro et al., 2023). Results from the clinical validation component of this study constitute the basis of another paper in this issue (Khaled et al., 2023).…”
Section: The World Mental Health Qatar (Wmhq) Studymentioning
confidence: 99%